Implication of job satisfaction and organizational commitment on employee loyalty in manufacturing companies - Ismail, Haikal (2013)
The purpose of this study is to examine the implication of job satisfaction and organizational commitment on employees' loyalty in manufacturing companies in Malaysia In present study, Three objectives of the study have been developed. The first objective is to investigate the current level of job satisfaction, organizational commitment and employee loyalty of employees in manufacturing companies in Malaysia. Second, the study aim to examine the significant differences of the study variables (i.e. job satisfaction, organizational commitment and employee loyalty) within demographic factors such as gender, age, etc. Lastly, the study aims to examine the relationships of the study variables. The results of study indicated that employees in manufacturing companies have moderate job satisfaction, moderate level of organizational commitment and slightly low level of employee loyalty. The results also revealed that the study variables have no significant differences within demographic factors. Lastly, the study found that job satisfaction and organizational commitment have significant impact on employee loyalty. Based on these findings, recommendations for manufacturing companies and for further study have been proposed.